CLIL AS AN INNOVATIVE APPROACH TO LANGUAGE TEACHING - Gulyamova Mavluda Khamitovna (Bright Mind Publishing, 2026)
Content and Language Integrated Learning (CLIL) is an innovative approach to language teaching that develops both subject knowledge and language skills at the same time. The article defines advantages of CLIL in language teaching, integrating content with language learning, CLIL provides meaningful and authentic learning situations that increase learner engagement, critical thinking, and communication. Studies show that CLIL improves language skills, especially writing, vocabulary, and interaction, when learner-centered strategies are used. Overall, CLIL goes beyond traditional language teaching by focusing on real-life communication and interdisciplinary learning, making language learning more effective and meaningful.
Keywords: Communication, engagement, content, integration, input, output, language, learning, meaningful, subject.